ЛИРИКАЛЫҚ ШЫҒАРМАЛАРДА ТЫНЫШЛЫҚ ТЕМАСЫ (Шайыр Өсербай Әлеўов дөретиўшилиги мысалында) - Жиемуратова, А.С. (FAN va JAMIYAT, 2022)
In this article, you will learn about the thougts of the poet Userbay Aleuov about peace and tranquility. In the poet's lyrics you will learn about the wars that try to disrupt peace, the harm of nuclear weapons to humanity and the whole world, the disturbance of balance in nature. It tells about the poet's philosophical thoughts on the preservation of the planet and peace.